2017
DOI: 10.1002/cplu.201600554
|View full text |Cite
|
Sign up to set email alerts
|

p‐Phosphonated Calix[n]arene Stabilizes Superparamagnetic Nanoparticles for Nitrate and Phosphate Uptake

Abstract: Supporting informationand the ORCID identification number(s) for the author(s) of this article can be found underh ttp://dx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 52 publications
2
4
0
Order By: Relevance
“…This study also showed that uncoated magnetite has similar phosphate removal efficiencies to that of PCalix[n] coated magnetite, highlighting that the iron‐magnetite is the primary reason for the phosphate removal. On the other hand, PCalix[n] coatings were found to be mainly effective for the removal of nitrate ions . The phosphate removal efficiency of the iron‐magnetite was also presented by other studies in our research group .…”
Section: Microalgal Composites With Magnetic Nanoparticlessupporting
confidence: 78%
See 4 more Smart Citations
“…This study also showed that uncoated magnetite has similar phosphate removal efficiencies to that of PCalix[n] coated magnetite, highlighting that the iron‐magnetite is the primary reason for the phosphate removal. On the other hand, PCalix[n] coatings were found to be mainly effective for the removal of nitrate ions . The phosphate removal efficiency of the iron‐magnetite was also presented by other studies in our research group .…”
Section: Microalgal Composites With Magnetic Nanoparticlessupporting
confidence: 78%
“…In a recent study, p ‐phosphonated calix[n]arene (PCalix[n]) coated superparamagnetic nanoparticles were effective in removing up to 62% of nitrate‐nitrogen and 48% of phosphate ions from an aqueous effluent within 24 h . This study also showed that uncoated magnetite has similar phosphate removal efficiencies to that of PCalix[n] coated magnetite, highlighting that the iron‐magnetite is the primary reason for the phosphate removal.…”
Section: Microalgal Composites With Magnetic Nanoparticlesmentioning
confidence: 78%
See 3 more Smart Citations